Evaluation of Rat's Attack (Rattus argentiventer Robb & Kloss) After Release of Owl (Tyto alba) in Deli Serdang - Ema Rosalina Sipayung; Suzanna Fitriany Sitepu; Fatimah Zahara (Jurnal Agroekoteknologi, 2018)
Rat is the important rice pests. Damageon rice crops caused by rat's attack in Indonesia reached a loss of 15-20% every year. This research aims to find out the rat's attack after release of owls. This research was conducted in Desa Sidodadi Ramunia and Desa Baru Deli Serdang with the distance about 22 km. This research was conducted   from May until December 2016.This research  used a survey method. Determination of research areas with purposive sampling method.Determination sample area using diagonal sampling method.Analyzed using Spearman's rank. The results show that the  active rat's nest in Desa Baru is more than Sidodadi Ramunia, it was on age 40 days after planting (hst) in Desa baru there are 18 active nest while in Desa Sidodadi Ramunia none active rat's nest. The highest percentage of attacks was found in Desa Baru with moderate category (27.5%) , and the lowest in Desa Sidodadi Ramunia (0%). Thehighest production was   in Desa Sidodadi Ramunia (5.71 tons/ha)and  the lowest production was inDesa Baru (3.11 tons/ha). Correlation result showed that the corelation value of the active rat's nest with the percentage of rat's attackis 0.917,  correlation value of amountowl with active rat's nest is  - 0.928,  correlation value amount of owl with the percentage of rat's attack - 0.866 and correlation value offarmer's perception to controling rat's attack with crop production is 0.810.Keywords: Rattus argentiventer, rat's nest,Tyto alba